DOAP1 Promotes Flowering in the Orchid Dendrobium Chao Praya Smile - Sawettalake, Nunchanoke; Bunnag, Sumontip; Wang, Yanwen; Shen, Lisha; Yu, Hao (Frontiers in Plant Science, 2017)
APETALA1 (AP1) encodes a key MADS-box transcription factor that specifies the floral meristem identity on the flank of the inflorescence meristem, and determines the identity of perianth floral organs in the model plant Arabidopsis thaliana. Orchids are members of the Orchidaceae, one of the largest families of angiosperms. Although the expression patterns of a few AP1-like genes in orchids have been reported, their actual functions in orchid reproductive development are so far largely unknown. In this study, we isolated and characterized an AP1 ortholog, DOAP1, from Dendrobium Chao Praya Smile. DOAP1 was highly expressed in reproductive tissues, including inflorescence apices and flowers at various developmental stages. Overexpression of DOAP1 resulted in early flowering in Arabidopsis, and was able to rescue the floral organ defects of Arabidopsis ap1 mutants. Moreover, we successfully created transgenic Dendrobium Chao Praya Smile orchids overexpressing DOAP1, which displayed earlier flowering and earlier termination of inflorescence meristems into floral meristems than wild-type orchids. Our results demonstrate that DOAP1 plays an evolutionarily conserved role in promoting flowering and floral meristem specification in the Orchidaceae family.